2022
DOI: 10.1002/bimj.202100293
|View full text |Cite
|
Sign up to set email alerts
|

A sequential test for assessing the effectiveness of response strategies during an emerging epidemic

Abstract: This article has earned an open data badge "Reproducible Research" for making publicly available the code necessary to reproduce the reported results. The results reported in this article could fully be reproduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Indeed, it has been suggested that mild and long-term lockdown strategies had limited power and lowered efficiency in containing the disease in general as compared to strict and short-term lockdown 35 . Especially when infections overwhelm the healthcare system, the fatality rate can be surprisingly high due to inadequate medical resources 36 , 37 . The rtaCFR then declined gradually since January 2021 with a small peak of around 0.02 observed during the third wave in June 2021 dominated by the Delta variant.…”
Section: Simulation Studiesmentioning
confidence: 99%
“…Indeed, it has been suggested that mild and long-term lockdown strategies had limited power and lowered efficiency in containing the disease in general as compared to strict and short-term lockdown 35 . Especially when infections overwhelm the healthcare system, the fatality rate can be surprisingly high due to inadequate medical resources 36 , 37 . The rtaCFR then declined gradually since January 2021 with a small peak of around 0.02 observed during the third wave in June 2021 dominated by the Delta variant.…”
Section: Simulation Studiesmentioning
confidence: 99%